Financial Literacy in MSMEs: Evidence from Creative Economy Entrepreneurs in Jakarta - Gunawan, Aristo Surya; Cahayani, Ati (Yayasan Sinergi Kawula Muda, 2026)
There is a phenomenon that Micro, Small, and Medium Enterprises (MSMEs) difficult to grow and face bankruptcy might due to lack of financial knowledge. Financial literacy is crucial for MSMEs which it serves as a foundation that enables MSMEs entrepreneurs to manage their financial resources more effectively, which ultimately contributes to the sustainable growth of their businesses. This study aims is to identify a descriptive overview the level of financial literacy among creative economy MSME entrepreneurs in Jakarta. This research using a descriptive quantitative data analysis. Quantitative data were collected through the distribution of questionnaires to 70 respondents. The quantitative data analysis using the overall mean score technique. The findings indicate that the respondents demonstrate positive level of financial literacy with all dimensions tested under “agree”, particularly in awareness of value for money, financial discipline, planning and preparedness. However, respondents’ financial literacy remains at basic stage, and still limited in more advanced financial instruments and capital market activities.